Age-related changes in intestinal permeability and absorptive capacity in the domestic cat (Felis catus) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Manawatū, New Zealand - Patterson, Keely (Massey University, 2025)
Ageing reduces fat and protein digestibility in the domestic cat which might have implications for their health and wellbeing. Reasons for the reduction in digestibility are unknown, but could be related to changes in the structure and/or function of the gastrointestinal tract (GIT), including increased permeability. Increased intestinal permeability may affect nutrient absorption, promote inflammatory responses, and allow pathogens to be absorbed. Currently, the literature that describes the relationship between intestinal permeability and age is conflicting, with limited studies undertaken in the domestic cat. This thesis compiled the first literature review of intestinal permeability and absorptive capacity, focusing on the lack of meaningful information and a standardised methodology regarding these GIT parameters in cats. It is hypothesised that intestinal permeability is negatively affected by age, and that interventions, such as probiotics, can reverse this. In Chapter 2, the differential sugar absorption test (SAT), using lactulose, rhamnose, xylose, and 3-O methylglucose (3-OMG) as markers of intestinal permeability and absorptive capacity, was developed using liquid chromatography-mass spectrometry (LC-MS). By using this method in Chapter 3, a group of young cats were compared to a group of senior cats. The results supported the hypothesis that intestinal permeability increased in senior cats. There was no age-related change in absorptive capacity, but there was a trend where males tended to have higher absorptive capacity values than females. To further understand GIT health in ageing cats and test possible interventions to strengthen the weakened intestinal barrier, probiotic yeast Saccharomyces cerevisiae var. boulardii (S. boulardii) was supplemented to midlife – senior aged cats in a crossover trial in Chapter 4. S. boulardii supplementation did not affect the GIT health parameters measured. Secondary analysis showed that with increasing age, the cats faced reduced fat digestion and increased intestinal permeability. This study highlighted the variation in data sets obtained in senior cats which should be accounted for in future research. Additionally, future research should focus on the mechanism by which altered intestinal permeability decreases nutrient digestibility to promote better nutrition for senior cats.
Keywords: Intestinal permeability, absorptive capacity, liquid chromatography-mass spectrometry (LC-MS), metabolome, pet nutrition; 300303 Animal nutrition